Comment to Pazos et al. (2019) “The oldest record of a tyreophoran track in Gondwana: Geological implications of subaerial exposure in the lower part of the Lajas Formation at the Covunco section (Neuquén Basin), Patagonia, Argentina" - Ponce, Juan J. (2020)
Fil: Ponce, Juan J. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología; Argentina.